Explicație pas cu pas:
[tex]x=1,(6)+ \frac{1}{3}+1 = \frac{16 - 1}{9} + \frac{1 + 3}{3} = \frac{15}{9} + \frac{4}{3} = \frac{5}{3} + \frac{4}{3} = \frac{9}{3} = 3[/tex]
[tex]y=|-2,7+1,5|+ \frac{1}{5} = | - 1,2| + \frac{1}{5} = 1,2 + \frac{1}{5} = \frac{6}{5} + \frac{1}{5} = \frac{7}{5} [/tex]
[tex]z=|2 - \frac{2}{3} |-|- \frac{5}{12} + \frac{1}{4} |- \frac{1}{3} = | \frac{6 - 2}{3} | - | \frac{ - 5 + 3}{12} | - \frac{1}{3} = | \frac{4}{3} | - | - \frac{2}{12} | - \frac{1}{3} = \frac{4}{3} - \frac{1}{6} - \frac{1}{3} = \frac{8 - 1 - 2}{6} = \frac{5}{6} [/tex]
[tex] \frac{5}{6} < \frac{7}{5} < 3 = > z < y < x[/tex]